Pyogenic Granuloma of the facial skin: a case report - F. A. Oredugba; O. F. Ajayi (Nigerian Dental Journal)
Pyogenic granuloma is an exophytic lesion which arises as a result of an exuberant connective tissue reaction to a known stimulus or injury. Common sites of presentation include oral mucosa, face and fingers. It may occour at any age but mostly in the second decade of life and more common in females. Surgical excision, Nd: YAG laser, flash lamp pulsed dye laser, intralesional injection of ethanol or corticosteroid and sodium tetradecyl sulfate sclerotherapy are treatment options which have been proposed for the lesion. Pyogenic granuloma of the facial skin has been rarely reported in our environment. This report describes the condition in a 10 year-old male referred for investigation of possible pathology from the teeth and management. It developed consequent to constant trauma to a pimple at the lower left border of the mandible. Predisposing factors, clinical features, histology and management are discussed.